2016
DOI: 10.1007/s00726-016-2352-7
|View full text |Cite
|
Sign up to set email alerts
|

β-Conglycinin enhances autophagy in porcine enterocytes

Abstract: β-Conglycinin (β-CG) is well known for inducing intestinal allergies and dysfunction in neonates and young pigs. However, the underlying mechanisms are largely unknown. In this study, to clarify the role of autophagy in β-CG-induced cytotoxicity, we investigated the effects of β-CG on cell viability and autophagy activity in porcine enterocytes (IPEC-1 cells). The results indicated that the cell viability was decreased with the increasing levels of β-CG. β-CG treatment enhanced the eGFP-LC3 puncta per cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This finding provides an important clue into the underlying mechanism whereby β-CG exerts adverse effects, although alteration in autophagic activity needs to be directly measured in future studies. Yi et al 11 reported that β-CG enhanced enterocyte autophagy in vitro. To date, there is little information on the relationship between β-CG and intestinal autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…This finding provides an important clue into the underlying mechanism whereby β-CG exerts adverse effects, although alteration in autophagic activity needs to be directly measured in future studies. Yi et al 11 reported that β-CG enhanced enterocyte autophagy in vitro. To date, there is little information on the relationship between β-CG and intestinal autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, β-CG enhanced LC3-II expression and autophagy in IPEC-1 cells. 7 Although these studies have provided evidence that several downstream pathways are implicated in β-CG-induced intestinal injury in pigs, the underlying regulatory mechanisms are not fully understood. A previous study analyzed the proteomic expression profile of β-CG-induced porcine intestinal cells using twodimensional gel electrophoresis and reported that 14 proteins were differentially expressed.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Peng et al found that β-CG decreased tight junction distribution and promoted cell death in porcine intestinal epithelial cells via the MAPK/NF-κB signaling pathway . In addition, β-CG enhanced LC3-II expression and autophagy in IPEC-1 cells . Although these studies have provided evidence that several downstream pathways are implicated in β-CG-induced intestinal injury in pigs, the underlying regulatory mechanisms are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation